Curative efficacy of entomopathogenic nematodes against white grubs in honeysuckle fields - Li, Xia; Men, Xingyuan; Wang, Jianhua; Lv, Suhong; Li, Lili; Cui, Hongying; Song, Yingying; Fang, Xinsheng; Song, Zhenqiao; Guo, Wenxiu; Yu, Yi (Frontiers in Sustainable Food Systems, 2023)
Root-feeding white grubs are one of the most serious pests of honeysuckle trees (Lonicera japonica) in China, directly damaging their roots and facilitating infection by soil pathogens. Entomopathogenic nematodes (EPNs) are considered as potential control agents against soil-dwelling insect pests. This study aimed to identify effective EPN species against white grubs through bioassay and field experiments. Among the EPN species screened against Holotrichia oblita under laboratory conditions, Steinernema feltiae and Heterorhabditis indica had low virulence, while S. longicaudum, S. glaseri, and H. bacteriophora applied at a rate of 400 IJs/larva caused a higher corrected mortality (80.00 ± 5.77%), which screened them as good candidates for future applications. The field experiments showed that both S. longicaudum and H. bacteriophora were approximately as effective in reducing white grubs as the insecticide phoxim, whereas S. glaseri caused a significantly lower reduction compared with these two EPNs and phoxim. Plant mortalities obtained from S. longicaudum, H. bacteriophora and the insecticide treatment plots were significantly lower than those observed in the water-treated control plots. All EPNs examined could establish well in the treated honeysuckle fields for 42 d, confirmed by Tenebrio molitar larvae baiting technique. Our findings suggest that EPNs could provide curative efficacy against white grubs and significantly reduce plant death in honeysuckle fields.